Effects of energy level, reconstruction kernel, and tube rotation time on Hounsfield units of hydroxyapatite in virtual monochromatic images obtained with dual-energy CT - Jeong, Dae-Kyo; Lee, Sam-Sun; Kim, Jo-Eun; Huh, Kyung-Hoe; Yi, Won-Jin; Heo, Min-Suk; Choi, Soon-Chul (Imaging science in dentistry, 2019)
This study was performed to investigate the effects of energy level, reconstruction kernel, and tube rotation time on Hounsfield unit (HU) values of hydroxyapatite (HA) in virtual monochromatic images (VMIs) obtained with dual-energy computed tomography (DECT) (Siemens Healthineers, Erlangen, Germany). A bone density calibration phantom with 3 HA inserts of different densities (CTWATER®; 0, 100, and 200 mg of HA/cm ) was scanned using a twin-beam DECT scanner at 120 kVp with tube rotation times of 0.5 and 1.0 seconds. The VMIs were reconstructed by changing the energy level (with options of 40 keV, 70 keV, and 140 keV). In order to investigate the impact of the reconstruction kernel, virtual monochromatic images were reconstructed after changing the kernel from body regular 40 (Br40) to head regular 40 (Hr40) in the reconstruction phase. The mean HU value was measured by placing a circular region of interests (ROIs) in the middle of each insert obtained from the VMIs. The HU values were compared with regard to energy level, reconstruction kernel, and tube rotation time. Hydroxyapatite density was strongly correlated with HU values (correlation coefficient=0.678, <0.05). For the HA 100 and 200 inserts, HU decreased significantly at increased energy levels (correlation coefficient= -0.538, <0.05) but increased by 70 HU when using Hr40 rather than Br40 (correlation coefficient=0.158, <0.05). The tube rotation time did not significantly affect the HU ( >0.05). The HU values of hydroxyapatite were strongly correlated with hydroxyapatite density and energy level in VMIs obtained with DECT.